2015
DOI: 10.1088/0004-637x/803/2/53
|View full text |Cite
|
Sign up to set email alerts
|

Gas Phase Synthesis of (Iso)quinoline and Its Role in the Formation of Nucleobases in the Interstellar Medium

Abstract: Nitrogen-substituted polycyclic aromatic hydrocarbons (NPAHs) have been proposed to play a key role in the astrochemical evolution of the interstellar medium, yet the formation mechanisms of even their simplest prototypes -quinoline and isoquinoline-remain elusive. Here, we reveal a novel concept that under high temperature conditions representing circumstellar envelopes of carbon stars, (iso)quinoline can be synthesized via the reaction of pyridyl radicals with two acetylene molecules. The facile gas phase fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Mechanismsh ave been proposed for the synthesis and growth of homocyclic aromatics in the isolated phase, [7,8] and even for the growth of nitrogen-substituted analogues. [9] However,t he mechanism of introduction of nitrogen into the ring scaffold remains elusive, [10,11] because higher barriers and unfavorable energetics make the growth reactions of nitrogen analogues unlikely.F urthermore, even condensed-phase processes are deemed less likely to yield thymine from pyrimidine than, for example, adenine from purine. [12] The most stable thymine tautomer is the diketo form in the gas phase, and the abundance of the most stable enolic form, lying around 45 kJ mol À1 above the diketo isomer, [13] is negligible at temperatures at which thymine is stable.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanismsh ave been proposed for the synthesis and growth of homocyclic aromatics in the isolated phase, [7,8] and even for the growth of nitrogen-substituted analogues. [9] However,t he mechanism of introduction of nitrogen into the ring scaffold remains elusive, [10,11] because higher barriers and unfavorable energetics make the growth reactions of nitrogen analogues unlikely.F urthermore, even condensed-phase processes are deemed less likely to yield thymine from pyrimidine than, for example, adenine from purine. [12] The most stable thymine tautomer is the diketo form in the gas phase, and the abundance of the most stable enolic form, lying around 45 kJ mol À1 above the diketo isomer, [13] is negligible at temperatures at which thymine is stable.…”
Section: Introductionmentioning
confidence: 99%
“…23 The formation of N-substituted analogs is much less understood and only few reactions have been investigated so far that could potentially yield heterocyclic molecules. For example, Parker et al reported a ring growth step connecting pyridine with quinoline, 24,25 which explains PANH growth, but not the introduction of nitrogen into the PAH scaffold. Unveiling the formation pathways of PANHs helps mitigate the emissions of these carcinogens in our terrestrial environment and understand their formation and large abundance in the interstellar medium and in Titan's atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative reaction mechanism has recently been proposed in which nitrogen atoms are incorporated within a bicyclic aromatic system through a series of radical-mediated gas phase reactions (Parker et al 2015). Here, (iso)quinoline (C 9 H 7 N; Scheme 1) was shown to be formed through the hydrogen-abstraction acetylene-addition (HACA) pathway involving pyridyl radicals (C 5 H 4 N) and acetylene (C 2 H 2 ) at elevated temperatures of up to 1500 K. Nitrogen atom incorporation has been shown to occur in mono and bicyclic six-membered carbon rings via ion-molecule reactions (Hamid et al 2014a(Hamid et al , 2014b, however, not via bimolecular reactions under single collision conditions as is characteristic for cold molecular clouds.…”
Section: Introductionmentioning
confidence: 99%